Penanganan Konflik Ambon dalam Analisis Dialektics Peace-Reconciliation dari Bar- Siman-Tov - Shofiyah, St.; Cangara, Hafied (Al-MUNZIR, 2023)
Abstract The concept of conflict management often focuses only on how to stop the conflict. However, how to prevent these conflicts from happening again, and how to maintain permanent peace, often escapes scientific studies and the attention of conflict theorists and parties concerned with world peace. Based on this phenomenon, Bar-Siman-Tov developed a theory regarding the creation of lasting peace (stable peace) through a dialectic between the "peace approach" (top down structural) and the "reconciliation approach" (bottom up social psychological). The research is aimed at analyzing the Ambon conflict using the Bar-Siman-Tov theory. The Ambon conflict is a big story in the history of the Indonesian nation. Maluku,  known as a peaceful region with all its plurality, was tested in 1999-2002 by a major conflict. The method used is the library method by collecting data through various written sources. The results of the study show that the dialectic of a structural "peace approach" with a grassroots "reconciliation approach" is capable of creating stable peace. Keywords: stable peace; peace; reconciliation; dialectics